2018
DOI: 10.1021/acschemneuro.8b00268
|View full text |Cite
|
Sign up to set email alerts
|

Local GABAA Receptor-Mediated Suppression of Dopamine Release within the Nucleus Accumbens

Abstract: Benzodiazepines make up a class of psychoactive drugs that act as allosteric co-activators of the inhibitory GABA A receptor. These drugs are useful for the treatment of several psychiatric disorders but also hold considerable abuse liability. Despite the common use and misuse of benzodiazepines, the mechanisms through which these drugs exert their reinforcing effects remain incompletely understood. Transient phasic increases in dopamine levels are believed to play an important role in defining the reinforcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…Similar to other GABAR-focused studies using brain slices (Brodnik, Batra, Oleson, & Espana, 2019;Galeffi, Sah, Pond, George, & Schwartz-Bloom, 2004;Schmidt, Boller, Ozen, & Hall, 2001;Vizuete et al, 2019;Wollman, Levine, & Fregosi, 2018), muscimol was used as the agonist to examine differences in GABA A R functionality associated with PNE. Muscimol is known to exhibit high affinity for synaptically located GABA A R receptors comprised of two α 1-6 , two β 1-4 and one subunit of γ 1-3 δ, ε, ϴ or π, however, it also acts as a partial agonist at the GABA Aρ R subtype (Connolly & Wafford, 2004;Kusama et al, 1993;Woodward, Polenzani, & Miledi, 1993).…”
Section: Gaba Aρ Rmentioning
confidence: 99%
“…Similar to other GABAR-focused studies using brain slices (Brodnik, Batra, Oleson, & Espana, 2019;Galeffi, Sah, Pond, George, & Schwartz-Bloom, 2004;Schmidt, Boller, Ozen, & Hall, 2001;Vizuete et al, 2019;Wollman, Levine, & Fregosi, 2018), muscimol was used as the agonist to examine differences in GABA A R functionality associated with PNE. Muscimol is known to exhibit high affinity for synaptically located GABA A R receptors comprised of two α 1-6 , two β 1-4 and one subunit of γ 1-3 δ, ε, ϴ or π, however, it also acts as a partial agonist at the GABA Aρ R subtype (Connolly & Wafford, 2004;Kusama et al, 1993;Woodward, Polenzani, & Miledi, 1993).…”
Section: Gaba Aρ Rmentioning
confidence: 99%
“…Bath application of -Ctx increases dopamine release in adolescents, indicating that blocking 6 nAChRs leads to disinhibition of dopamine release in adolescents, but not adults. GABA has been shown to inhibit terminal dopamine release (Pitman et al, 2014;Melchior et al, 2015;Brodnik et al, 2019;Lopes et al, 2019) indicating that -Ctx could be reducing GABA tone in adolescents. In addition, some striatal GABA interneurons express nAChRs (see Tepper et al, 2018)( Figure 4C).…”
Section: Nachrs Particularly α6-containing Nachrs Differentially Momentioning
confidence: 99%
“…(C) We next hypothesized that the age-related differences in 6-containing nAChR-modulation of dopamine release may be mediated by -Ctx causing reduction of GABA signaling in adolescents. GABA receptors regulate dopamine release (Brodnik et al, 2019) and nAChRs are found on GABA interneurons (Tepper et al, 2018). A schematic shows potential localization of nAChRs and GABA receptors in the nucleus accumbens core.…”
Section: Nachrs Particularly α6-containing Nachrs Differentially Momentioning
confidence: 99%
“…Importantly, local microcircuitry gates dopamine at the terminals, regulating the magnitude, spread, timing, and duration of dopamine signals 7 . A range of local homosynaptic and heterosynaptic mechanisms directly regulate dopamine at striatal terminals 7 , including striatal GABA tone [8][9][10] . Given the dynamic activity of LTSIs during reward retrieval, we hypothesized that LTSIs might provide a novel GABAergic mechanism of local dopamine regulation in the striatum with significant implications for learning.…”
mentioning
confidence: 99%
“…Growing evidence points to a clear role of tonic GABA signaling locally modulating dopamine release in the striatum via both GABA A and GABA B transmission [8][9][10] . As LTSIs are tonically active in striatal slices, they are a compelling candidate source for this modulatory GABAergic tone.…”
mentioning
confidence: 99%